Pembelajaran Interaktif Melalui Pendampingan Penggunaan Game Edukatif Berbasis Scratch Pada Siswa - Nur Adila Syahid; Aisyah Nursyam; Sirwanti; Andi Trisnowali MS (Rengganis Jurnal Pengabdian Masyarakat, 2025)
The rapid development of information technology requires the education sector to adapt to more interactive and innovative digital-based learning. One effective medium is Scratch, a visual programming application that is easy to use for creating educational games. However, at SD Negeri 02 Paluhombo, learning is still predominantly conducted using conventional methods, causing students to quickly lose interest and lack motivation. Based on this problem, this community service activity aimed to improve students’ conceptual understanding through guided use of educational games based on Scratch. The method employed was Community Based Participatory Research (CBPR), involving active participation of fifth and sixth grade students in five stages: problem identification, collaborative planning, implementation of guidance, evaluation, and follow-up. The instruments used included pre-tests, post-tests, and student satisfaction questionnaires. The evaluation results showed that all students experienced an improvement in learning outcomes after the intervention. Pre-test and post-test results were used to measure students' conceptual understanding, while satisfaction questionnaires assessed students’ responses to the guidance process. The Wilcoxon test showed significant values of 0.026 for Grade V and 0.001 for Grade VI (p < 0.05), indicating a significant difference between pre-test and post-test scores. The guidance on using Scratch-based educational games proved effective in enhancing students' conceptual understanding